Prevođenje oznaka kohezije kao pokazatelj razine prevođenja - Antunović, Goranka (1997)
Sažetak na engleskom: Departing from Brown and Yule's (1984)interpretation of cohesion in the light of the distinction between text-as-product and discourse-as-process, the article relates interpretation of cohesion markers to the choice of their translation equivalents. When a cohesion marker is interpreted as a word whose 'forever given' meaning is the same as that of its formal correspondent, the correspondent appears as the obligatory translation equivalent (except when the antecedent grammatically requires a different solution, in which case an alloform is normally used). However, if a cohesion marker is seen as an indicator of a semantic relaitonship, it can be translated by any other word/phrase indicating the same relationship. The postulated interdependence between the understanding of cohesion and the level of translation (text vs. discourse) is tested on a number of Swedish-to-Croatian translations. The analysis focuses on translation equivalents of Swedish pronouns, conjunctions -och- and -men-, and a number of connective adverbs. Against that background, the final section singles out some typical examples of text-level interpretation and translation of cohesion markers.
ENG